Occurrence and Identification of Pathogenic Vibrio Contaminants in Common Seafood Available in a Chinese Traditional Market in Qingdao, Shandong Province - Song, Xinjie; Zang, Jinlin; Yu, Weisen; Shi, Xuexiang; Wu, Yongning (Frontiers in Microbiology, 2020)
The investigation of the causative agents for foodborne diseases and subsequent development of preventive steps to control the outbreak and related economic loss is the basic goal and priority of a rational food safety program. The entero-pathogenic Vibrio spp., which are Gram negative bacteria inhabiting estuarine ecosystems, are the major cause of foodborne illness associated with the consumption of raw or undercooked contaminated seafood or shellfish. To survey the Vibrio contamination in sea snails (Neptunea cumingi Crosse and Busycon canaliculatu), a total of 20 samples were collected from traditional market, at Qingdao city in Shandong province, China and analyzed for Vibrio species contamination. Presumptive-positive colonies grown on a specific Vibrio agar-based medium were picked and identified by the VITEKTM. Vibrio alginolyticus, V. parahaemolyticus, and V. vulgaris were isolated and identified in 11, 8, and 2 seafood samples, respectively. Among the 8 isolates of V. parahaemolyticus. The V. parahaemolyticus isolates were further tested for the tdh, trh, and tlh virulence factors. All the V. parahaemolyticus isolates were tlh-positive, however, all of them were tdh-negative. Interestingly 2 V. parahaemolyticus isolates were positive for trh virulence factor. These results indicated that there is a high incidence of V. alginolyticus and V. parahaemolyticus in sea snails. Therefore, food safety regulations for fishery auction markets should be established to control these species in addition to other Vibrio pathogenic contaminants. Our study provides the first evidence for the prevalence of Vibrio spp. in sea snail samples from traditional market in the Qingdao province of China.